Ecological control of exotic annuals in native C3 grass swards. (23rd July 2018) - Cole, Ian; Koen, Terry; Prober, Suzanne; Lunt, lan
Abstract: While the mechanisms behind the control of exotic annuals by C4 native grasses on soils of low fertility are well understood, it is not clear how C3 native grasses sometimes achieve similar levels of control. In earlier research (Cole I. A., et al., 2016a, Aust. Ecol .41, 40; Cole I. A., et al., 2016b, Restor. Ecol .24, 354), the abundance of cool season exotic annuals waxed and waned over time, apparently in response to changes in the abundance of the tall C3 native grass ( Austrostipa species) which at times dominated the understorey. This study used multiple linear regression and structural equation models to compare the relative influence of the abundance of the native grass sward (in autumn and spring), soil nitrate (in autumn) and the presence or absence of litter (in autumn) on the abundance in spring of exotic annual broadleafs and grasses. The most important controls of exotic annuals were native grass abundance and related soil nitrate reductions in autumn, when exotic annuals germinate. Another important control for exotic broadleafs was presence of litter in autumn. In contrast, the presence of litter promoted exotic annual grasses. Native grass abundance in spring (reflecting competition over the growing season of exotic annuals) appeared relatively unimportant. Key management objectives when attempting to control exotic annuals will be to maximize competition when exotic species are establishing by promoting the health and abundance of native grasses, and maintaining high levels of litter cover.